Audit Quality, Firm Value And Earnings Management - Deva Setyawan; Imam Ghozali (E-Jurnal Akuntansi, 2025)
There are fluctuations in global commodity prices that affect the performance of mining companies, thus encouraging management to carry out profit management to maintain the company's image and value. The research aims to find out empirically the mediated relationship of audit quality mediation to the company's value through profit management. The study was conducted on 59 companies in the mining sector listed on the IDX for the period 2021 –2023. The data analysis technique uses CEM estimation with directregression and mediation models. The findings of this research are that there is a negative influence on industry specialization and earning management. There is no evidence of the influence of audit firm size on earning management. There is a positive relationship between audit firm size and industry specialization on company value, but audit costs have not been shown to have a relationship with company value. The relationship of profit management has a negative influence on earning management. Mediation tests have proven that earning management mediates the influence of industry specialization and audit costs on a company's value, but it does not mediate the size of the audit firm.